The Majjhima Nikaya : Vol. iii - Pali Text Society; Davids, Rhys (London : Pali Text Society, 1960)
Commentary on the Buddhist canonical work.
Microfiche.
Keywords: Tripitaka. -- Commentaries; Buddhist monasticism and religious orders -- Rules